Measurement of compensatory reserve predicts racial differences in tolerance to simulated hemorrhage in women. Issue 1 (July 2018) - Wenner, Megan M.; Hinds, Kumba Adia; Howard, Jeffrey T.; Nawn, Corinne D.; Stachenfeld, Nina S.; Convertino, Victor A.
Abstract : BACKGROUND: The compensatory reserve measurement (CRM) has been established to accurately measure the body's total integrated capacity to compensate for physiologic states of reduced central blood volume and predict hemodynamic decompensation associated with inadequate tissue oxygenation. We previously demonstrated that African American (AA) women have a higher tolerance to reductions in central blood volume. Therefore, we tested the hypothesis that the CRM would identify racial differences during simulated hemorrhage, before the onset of traditional signs/symptoms. METHODS: We performed a retrospective analysis during simulated hemorrhage using lower-body negative pressure (LBNP) in 23 AA (22 ± 1 years; 24 ± 1 kg/m 2 ) and 31 white women (WW) (20 ± 1 years; 23 ± 1 kg/m 2 ). Beat-by-beat blood pressure (BP) and heart rate (HR) were recorded during progressive lower body negative pressure to presyncope. The BP waveforms were analyzed using a machine-learning algorithm to derive the CRM at each lower body negative pressure stage. RESULTS: Resting mean arterial BP (AA, 78 ± 3 mm Hg vs. WW, 74 ± 2 mm Hg) and HR (AA, 68 ± 2 bpm vs. WW, 65 ± 2 bpm) were similar between groups. The CRM progressively decreased during LBNP in both groups; however, the rate of decline in the CRM was less ( p < 0.05) in AA. The CRM was 4% higher in AA at −15 mm Hg LBNP and progressively increased to 21% higher at −50 mm Hg LBNP ( p < 0.05). However, changes in BP and HR were not different between groups. CONCLUSION: These data support the notion that the greater tolerance to simulated hemorrhage induced by LBNP in AA women can be explained by their greater capacity to protect the reserve to compensate for progressive central hypovolemia compared with WW, independent of standard vital signs. LEVEL OF EVIDENCE: Diagnostic test, level II.